The Effects of Colostrum Immunoglobulin on Strongyloides Infection in Mice - Rumokoy, Laurentius; Posangi, Jimmy; Turangan, Santi; Irianti, Ning; Toar, Wisie Lusia; Aban, Julio Lopez (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
This experiment was conducted to determine the effects of bovine colostrum IgG on mice infected with Larvae of Strongyloides venezuelensis (L3Sv). This experiment was a 2X2 factorial arrangement including two level of colostrum immunoglobulin-G and two level of endostatine. The parameters were fecal eggs and number of female adult in the gut. The data were statistically analyzed for the mean and standard deviation values, and the differences in treatment groups were subject to ANOVA, if the global differences were detected, a post-ANOVA with LSD test ensued. The development of female adult in the gut, for each group, was performed using Spearmanâs rho test. Results showed that colostrum immunoglobulin-G reduce very significantly (P<0.001) the number of eggs per gram feces than in the groups of infected animals treated with endostatine as well as in the mice injected with 3000 L3Vs only. While the reduction of female larvae was significant obtained (P<0.05) in colostrum treatment (L3Sv + colostrum IgG) in comparison with endostatine. It was concluded that the supplementation of immunogobuline-G through the animal digestive system had positively control the Strongyloides venezuelensis parasite infection. This result provides an insight to utilize IgG colostrum in animal husbandry to overcome the threat of parasitic worms infection.